IndoorDSL: uma abordagem baseada em MDE para o desenvolvimento de mapas de representação do espaço indoor - ANDRADE, Evaldo da Silva (2020)
Indoor space representation models can provide important information about architectural and semantic aspects of a given building. Which enables the use of this information to encourage the development of applications aimed at navigation and positioning within this type of environment, applications that are supported through indoor positioning systems that appear to optimize navigation, or even increase productivity, or aid people with disabilities, among other solutions. However, information about the environment and tools that enable the elaboration of the indoor environment representation model that contain the information that can be used to feed the navigation and positioning systems within those environments are not always available. Either when available they become prohibitive due to the logistical apparatus necessary for the design of the model, or they demand a significant effort through editing tools that combine geographic and architectural information through manual and repetitive editing of primitives that make up this environment, making the task become quite error prone. Therefore, this work presents the proposal of creating indoor space representation through Domain Specific Language, that through a graphical syntax with aspects of the domain, provides the possibility of indoor environment modeling at a high level of abstraction in order to enable users with none or regular knowledge about the domain to create their own models and perform transformations between different models. Therefore its development takes place within the scope of INavigS, a software infrastructure focused on indoor positioning and navigation. Despite providing numerous features, still presents some gaps, as in the case of the elaboration of the indoor space representation model. When applying the language in the context of INavigS, feedback is obtained from users regarding the use of language, identifying it as a satisfactory tool for maps creation which may represent the indoor environment.